A study on road public transport policies and planning in Metropolitan Manila 1970s to the present - Ines, Angela Kariza C.; Pena, Kenneth Joseph H.; Regidor, Jose Regin F. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
Metro Manila has been the subject of several major comprehensive transportation studies, the first of which sUifaced in the 19705. Similar issues are found, and similar recommendations are made. It must be investigated why failings have recurred throughout the years despite the numerous studies and proposed master plans. Hence, this study ventured to assess the state of Metropolitan Manila's road public transport policies and planning from the 1970s to the present. This study found that the recurring problems of the policies and planning in the road public transportation system in Metro Manila can be grouped into two major issues: weak institutions and inefficient use of road space. Subordinate to these are sub-issues that interplay and compound the parent issue. The sub-issues to weak institutions were found to be: administrat ion, technical capability and limited budget. While the sub-issues to road space inefficiency were found to be: weak intermodal complementation, inadequate infrastructure, high road space share of private vehicles, and weak route structure. These issues are systemic that require a systemic approach, that is, attempting to solve one, without addressing another, will not rid the system ofthe issue. Resolving these issues all begin with strong and technically capable institutions. With strong institutions and a budget for reforms to gain traction, the system should turn its attention to route structure, infrastructure, and modernization.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Urban transportation policy -- Philippines; Highway planning -- Philippines -- Manila